ANALISA CURAHAN KERJA PEREMPUAN PESISIR DALAM AGRIBISNIS IKAN DI LAPPA KECAMATAN SINJAI UTARA KABUPATEN SINJAI - Muhammad Kusnady Tabsir (OCTOPUS : JURNAL ILMU PERIKANAN, 2016)
The study aims to investigate the flow of female workforce in each subsystem of the fish agribusiness. The study was carried out in Lappa Village, North Sinjai District of Sinjai Regency. Thirty (30) family heads were purposively selected as samples out of a population of 298 families. The analysis framework is data analysis procedure including hypothesis testing of studied variable workflow. The study indicates that the contribution of the women workforce in the fish agribusiness economic activities is significant because it is greater than that of men. The income contribution of women workforce to the agribusiness activities significant as reflected by the combination of four types of household economic activities of the sample families; production-marketing, processing-marketing, production-processing-marketing, and marketing.